EFFECTIVE IMPLEMENTATION OF PERSONAL CARD FOR FORMING POSITIVE STUDENT BEHAVIOR IN SMA STATE 6 PADANGSIDIMPUAN - Nor Mita Ika Saputri (Ristekdik : Jurnal Bimbingan dan Konseling, 2016)
This thesis entitled "The Effectiveness of the Implementation of Personal Card to Establish Positive Behavior students at SMAN 6 Doctrine Padangsidimpuan years 2014-2015. Preparation of this paper is motivated importance of personal cards to form the positive behavior of students.The problems that exist in this thesis is how the implementation of personal cards to form positive behavior in SMAN 6 Padangsidimpuan. This study was conducted using instruments such test, questionnaire, and observation. Furthermore, the data were analyzed using SPSS statistical process 20:00The findings of this research are: 1) scores acquisition of personal cards, from the calculation in mind that the average value of positive behavior scores questionnaire experimental group that in 1407 on the stage of the pretest, at this stage of the pretest score was 1585, in a control class on stage pretest number 1045 and the post-test stage to consume score reaches 1337. With the average value is determined on the classification assessment, the positive behavior in the country sma 6 Padangsidimpuan are in either category. 2) interval comparison of results in the experimental stage is 60.08 experimental pretest posttest namely 79.62 and at this stage of the control group pretest posttest control group 59.88 and 71.82.Based on the above findings, it was concluded that the effectiveness of the personal card in shaping positive behavior of students at SMAN 6 Padangsidimpuan can be said to be good. Similar studies should be done against the background of different contexts in order to compare the findings of this research